Quelle réflexivité les étudiants ingénieurs ont-ils à propos de leurs pratiques d’apprentissage? Analyse d’écrits réflexifs et propositions pour le renforcement des capacités réflexives - Lucie Gouttenoire; Anaïs Loizon (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
While reflexivity has been seen as an essential skill in the humanities for several decades, the engineering sector is starting to investigate about this skill, as an interesting way of professionalization. But the lack of shared culture of reflexivity, as well as students’ interest for exact sciences coupled with their difficulties in considering their own action as an objet to be thought, make it difficult to design pedagogical devices aiming at enhancing reflective abilities. In this paper, we want to draw a picture of agricultural engineering students’ reflective abilities by analysing written reflections they produced about their learning practices and process during a study course on economic and financial analysis. We found very different levels of reflexivity, similarly to what is described in the humanities. Some students do write rich reflections, while others have difficulties in involving themselves in projective activities and, more noticeably, in inquiry-based learning enabling them to question their own ways of thinking. We identify different levers to enhance reflexivity: expressing oneself using incarnated speech positions, reinforcing one’s curiosity towards oneself and towards others, and facing difficulties or unprecedented situations. This work can be read as a theoretical and practical proposal to give substance to the reflexivity concept and to provide input for pedagogical reflection.